EVALUATION OF THE EFFICACY OF SIX DIFFERENT HAND SANITIZERS COMMONLY AVAILABLE ON THE INDIAN MARKET - REENA RAJKUMARI.B, (International Journal of Pharma and Bio Sciences, 2015)
Hand sanitizers have become one of the essentials in hospitals and day-to-day life. They have gained much popularity and have become a highly accepted form of personal hygiene because of the ease of use. In this study, we aim to test and compare six different commercial hand sanitizers commonly available in the Indian market. We compared the effects of these sanitizers on three different microorganisms, utilizing the FDA-approved (standardized) glove juice method and the suspension method. Among the six hand sanitizers “Bactorub®” was found to be an effective hand sanitizer followed by “Sterilium®”.